Consumo de crías de didélfidos por Micoureus paraguayanus (Didelphimorphia: Didelphidae) en el sudeste de Brasil - Pires, Mathias M. (2010)
In a study aiming to describe the diet of Micoureus paraguayanus in a southeastern Brazilian Cerrado (savannah-like) remnant, we found young didelphid remains in fecal samples from live-trapped adults. These findings uncovered either events of scavenging on dead young didelphids or infanticide adding to the knowledge on the dietary breadth and behavioral ecology of M. paraguayanus. © SAREM, 2010.